Preclinical Evaluation of a Bone-Marrow Autograft Culture Procedure for Generating Lymphokine-Activated Killer Cells in Vitro - Hans-Georg Klingemann; Heather Deal; Dianne Reid; Connie J Eaves (Canadian Journal of Infectious Diseases)
Despite the use of high dose chemoradiotherapy for the treatment of acute leukemia. relapse continues to be a major cause of death in patients given an autologous bone marrow transplant. Further augmentation of pretransplant chemotherapy causes life threatening toxicity to nonhematopoietic tissues and the effectiveness of currently available ex vivo purging methods in reducing the relapse rate is unclear. Recently, data from experimental models have suggested that bone marrow-derived lymphokine (IL-2)-activated killer (BM-LAK) cells might be used to eliminate residual leukemic cells both in vivo and in vitro. To evaluate this possibility clinically, a procedure was developed for culturing whole marrow harvests with IL-2 prior to use as autografts, and a number of variables examined that might affect either the generation of BM-LAK cells or the recovery of the primitive hematopoietic cells. The use of Dexter long term culture (LTC) conditions, which expose the cells to horse serum and hydrocortisone. supported LAK cell generation as effectively as fetal calf serum (FCS) -containing medium in seven-day cultures. Maintenance of BM-LAK cell activity after a further seven days of culture in the presence of IL-2 was also tested. As in the clinical setting. patients would receive IL-2 in vivo for an additional week immediately following infusion of the cultured marrow autograft. Generation ofBM-LAK activity was dependent on the presence of IL-2 and could be sustained by further incubation in medium containing IL-2. Primitive hematopoietic cells were quantitated by measuring the number of in vitro colony-forming progenitors produced after five weeks in secondary Dexter-type LTC. Maintenance of these 'LTC-initiating cells' was unaffected by lL-2 in the culture medium. These results suggest that LAK cells can be generated efficien tly in seven-day marrow autograft cultures containing IL-2 under conditions that allow the most primitive human hematopoietic cells currently detectable to be maintained.